2021
DOI: 10.1108/jiabr-10-2020-0311
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative investigation into crowdfunding framework as a source of financing for waqf land development

Abstract: Purpose This paper aims to inquire about the opinions and recommendations of various experts on the crowdfunding waqf model (CWM), particularly in terms of its suitability, applicability and prospect in the market. Design/methodology/approach This paper used primary data which are collected from semi-structured interviews conducted with several experts from various backgrounds. For examining the data, this paper has used thematic analysis. Findings The experts support the suitability of CWM in providing fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Moreover, a few studies also recommended crowdfunding based on the waqf model, especially in non-Muslim countries (Zain et al, 2019). Furthermore, by conducting semi-structured interviews with the experts, Hapsari et al (2022) also found that crowdfunding offers a sustainable fund source to develop waqf lands. In another case, Afroz et al (2019) declare that implementing crowdfunding for financing solar energy in Malaysian households is possible.…”
Section: Sem Methodmentioning
confidence: 99%
“…Moreover, a few studies also recommended crowdfunding based on the waqf model, especially in non-Muslim countries (Zain et al, 2019). Furthermore, by conducting semi-structured interviews with the experts, Hapsari et al (2022) also found that crowdfunding offers a sustainable fund source to develop waqf lands. In another case, Afroz et al (2019) declare that implementing crowdfunding for financing solar energy in Malaysian households is possible.…”
Section: Sem Methodmentioning
confidence: 99%
“…Mutawalli needs the help of financial managers who can calculate and mitigate risks so that the waqf funds given to the community do not run out (Billah & Saiti, 2017). A third party for waqf financial management is also needed to offer prospective waqifs about projects that waqf institutions will carry out through Islamic Microfinance schemes (Hapsari et al, 2022). Financial planning can help mutawalli to be responsible for the sustainable development of waqf, significantly cash and property waqf.…”
Section: Research Agenda 1: the Accountability Of Islamic Social Fina...mentioning
confidence: 99%
“…[ 41 ] discovered that the crowdfunding waqf model contributes to sustainability by providing financing resources to develop waqf lands influenced by crowd funders, interesting projects, promotions, and effective regulations. Several studies have analysed the role of zakat as an Islamic social finance mechanism but did not directly link its effect on sustainability.…”
Section: Literature Reviewmentioning
confidence: 99%